Clinical Characteristics and Short-Term Prognosis of Children With Antibody-Mediated Autoimmune Encephalitis: A Single-Center Cohort Study - Kang, Qingyun; Liao, Hongmei; Yang, Liming; Fang, Hongjun; Hu, Wenjing; Wu, Liwen (Frontiers in Pediatrics, 2022)
Background: The incidence and prevalence of autoimmune encephalitis (AE) in the pediatric patient is gradually increasing. The aim of this retrospective observational study was to investigate the clinical characteristics and short-term prognosis of children with Neuronal Surface antibody-mediated AE in Hunan Children’s Hospital. Methods: Antibody analysis of blood and/or cerebrospinal fluid was performed in suspected AE patients admitted to the Department of Neurology, Hunan Children's Hospital from June 2014 to June 2021. 103 patients were finally diagnosed with Neuronal Surface Antibody-Mediated AE and were enrolled in this study. The clinical data and corresponding demographic, clinical characteristics, laboratory and imaging data, treatment, and prognosis data were collected and analyzed . Results: In our study, 103 AE patients with neuronal surface antibody-positive were identified. The main subtypes of AE in our cohort is anti-NMDAR encephalitis. Children with anti-CASPR2 encephalitis, anti-GABABR encephalitis or anti-LGI1 encephalitis were rare. The most common clinical manifestations were mental behavioral disorders, seizures and involuntary movements in our AE patients, with seizures as the most common initial symptom .The brain magnetic resonance imaging (MRI) and electroencephalography (EEG) were performed in all patients, a total of 45 (43.7%) patients had abnormal MRI results. EEG were abnormal in 96 (93.2%) patients. All 103 patients were given the first-line immunotherapy, 21 of which were also treated with the combination of the second-line immunotherapy. All surviving patients were followed up for at least 6 months. Seventy-seven patients recovered completely, twenty-three had sequelae in different degrees, and three died. Eight patients had one or more relapses during the follow-up period. Conclusions: AE can occur in children of all ages.AE is a treatable disease, and most patients have a good response to immune therapy and a low mortality rate. Compared with the older children, infant and young children (≤ 3 years old ) with anti-NMDAR encephalitis have a higher incidence of fever and status epilepticus, more severe condition, higher PICU admission rate and worse prognosis. AE patients with a high maximum mRS score and admission to PICU may require the second-line immunotherapy. Keywords: autoimmune encephalitis, child, clinical characteristics, immunotherapy, prognosis